Validation of QTLs for seed weight in a backcross population derived from an interspecific cross in soybean [Glycine max (L.) Merr.]: VALIDATION OF QTLs FOR SEED WEIGHT IN SOYBEAN - SHIVAKUMAR MARANNA; GIRIRAJ KUMAWAT; ARTI YADAV; RAM MANOHAR PATEL; SANJAY GUPTA; GYANESH KUMAR SATPUTE; SURESH CHAND; SAYED MASROOR HUSAIN (Journal of Oilseeds Research, 2019)
Soybean [Glycine max (L.) Merr.] is a major oilseed crop of India. Seed weight is an important yield component trait which should be suitably optimized in soybean varieties to maximize productivity. To validate 100-seed weight quantitave trait loci (QTL), a backcross population of soybean was developed from a cross between wild species Glycine soja (Sieb. and Zucc.) and Indian soybean cultivar JS 335. The BC2 backcross population was evaluated for three yield component traits, namely 100-seed weight, number of seeds/plant and seed yield/plant in BC2F2, BC2F3 and BC2F4 generation. Six QTLs reported to be associated with 100-seed weight in soybean were selected for QTL validation. SSR markers linked with two major QTLs for 100-seed weight could be validated successfully. One QTL, on linkage group D1a between Satt580-Satt179, identified for 100-seed weight explained 19.18% of phenotypic variance for combined data of three years. The second QTL for 100-seed weight was identified on linkage group C2 between marker Sat_251 and Sat_238 which contributed 10.97 and 9.28% of phenotypic variance in year 2015 and 2016, respectively.